The USA maritime enforcement regime: a model for South Africa? - Wardley, Gordon (Institute of Marine and Environmental Law, 2023)
There has been much public debate within South Africa (RSA), especially since 1994, concerning the role of the South African National Defence Force (SANDF) now that peace is the order of the day. Coupled to this is the perennial issue of insufficient funds to pay for all the services the government is expected to provide, and at the level with which all are satisfied. One of the hardest hit departments, from a budgetary point of view, is the Department of Defence (DoD), with funds been shifted to meet the ever increasing demand for socio-economic upliftment at the expense of defence. At the base of any argument concerning the issue of defence versus socio-economic upliftment, is the question of whether massive expenditure for defence in a peacetime environment is justifiable, seen in the light that many South Africans still do not have secure homes, access to acceptable education, medical facilities and potable water.